PENGARUH LINGKUNGAN TERHADAP PERILAKU MACHIAVELLIANISM PADA TIM ORGANISASI - Yuliana Setyaningrum; Anniez Rachmawati Musslifah (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
In a dynamic modern era, organizational teams are an important concept in various fields of life, including in the world of work and group activities. The work environment and organizational culture can influence individual behavior, including the emergence of machiavellianism behavior. Machiavellianism is a trait that tends to be manipulative and lacks empathy for others. This study aims to explore the influence of environment on machiavellianism behavior in organizational teams. Using a desk study method, this research concludes that Machiavellianism can affect team dynamics, performance, and relationships between team members. Some of the key factors that influence Machiavellianism include aggression, egoism and manipulation. It is important for individuals with machiavellianism traits to avoid its negative impact and improve performance and collaboration in social and professional interactions.